Building robots with Lego Mindstorms NXT. - Ferrari, Mario; Ferrari, Giulio; Astolfo, David; Ferrari, Mario; ScienceDirect (Online service) (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2007)
The Ultimate Tool for MINDSTORMSʼ Maniacs The new MINDSTORMS kit has been updated to include a programming brick, USB cable, RJ11-like cables, motors, and sensors. This book updates the robotics information to be compatible with the new set and to show how sound, sight, touch, and distance issues are now dealt with. The LEGO MINDSTORMS NXT and its predecessor, the LEGO MINDSTORMS Robotics Invention System (RIS), have been called "the most creative play system ever developed." This book unleashes the full power and potential of the tools, sensors, and components that make up LEGO MINDSTORMS NXT. It also provides a unique insight on newer studless building techniques as well as interfacing with the traditional studded beams. Some of the world's leading LEGO MINDSTORMS inventors share their knowledge and development secrets. You will discover an incredible range of ideas to inspire your next invention. This is the ultimate insider's look at LEGO MINDSTORMS NXT system and is the perfect book whether you build world-class competitive robots or just like to mess around for the fun of it. Featuring an introduction by astronaut Dan Barry and written by Dave Astolfo, Invited Member of the MINDSTORMS Developer Program and MINDSTORMS Community Partners (MCP) groups, and Mario and Guilio Ferrari, authors of the bestselling Building Robots with LEGO Mindstorms, this book covers: Understanding LEGO Geometry Playing with Gears Controlling Motors Reading Sensors What's New with the NXT? Building Strategies Programming the NXT Playing Sounds and Music Becoming Mobile Getting Pumped: Pneumatics Finding and Grabbing Objects Doing the Math Knowing Where You Are Classic Projects Building Robots That Walk Robotic Animals Solving a Maze Drawing and Writing Racing Against Time Hand-to-Hand Combat Searching for Precision *Complete coverage of the new Mindstorms NXT kit *Brought to you by the DaVinci's of LEGO *Updated edition of a bestseller.
Placing and Fitting Gears; Using Pulleys, Belts, and Chains; Mounting Motors; Wiring Motors; -- Sensor Tips and Tricks; Designing Chassis, Modularity, and Load; Programming the RCX; Playing Sounds and Music; Wheeled Mobility Configurations; -- Building Pneumatic Systems; Configuring Gearboxes; -- Adding RCX Ports; Building Air Compressors; Finding and Grabbing Objects; Building Navigation Systems; -- Building Robots that Walk.
Previous ed.: published as Building robots with Lego Mindstorms. 2002.
Keywords: Robots; LEGO toys